2010
DOI: 10.24908/ss.v7i3/4.4157
|View full text |Cite
|
Sign up to set email alerts
|

‘You don’t have to be watched to make your toast’: Surveillance and Food Practices within Residential Care

Abstract: This paper explores forms of surveillance within residential care homes for young people. It is argued that surveillance is a crucial aspect of care and this can be experienced as both negative and positive by children and staff. In particular the research was concerned with how forms of control and monitoring are conducted in relation to food and food practices. Relations of power and resistance within the context of a care home are routinely played out and through food. The paper illustrates the ways in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
0
24
0
4
Order By: Relevance
“…First, while it is true, in the abstract, that in many areas associated with care (health care, child care, or elder care) those who are defined as marginalized are treated differently than those who are defined as able-bodied adults (Koskela 2012: 52) it should not be automatically assumed that surveillance in the context of care is negative. As noted, with some limited exceptions, such as research done on children in residential care in Scotland by McIntosh, Punch, Dorrer and Emond (2010), there are not a lot of accounts of surveillance that deal with care. McIntosh, Punch, Dorrer and Emond attribute the dearth of Surveillance Studies research devoted to care to the penchant for research focusing on the more ominous "big brother" and "panopticon" imagery associated with surveillance and control (2010: 290).…”
Section: Surveillance and Society 13(1) 52mentioning
confidence: 99%
“…First, while it is true, in the abstract, that in many areas associated with care (health care, child care, or elder care) those who are defined as marginalized are treated differently than those who are defined as able-bodied adults (Koskela 2012: 52) it should not be automatically assumed that surveillance in the context of care is negative. As noted, with some limited exceptions, such as research done on children in residential care in Scotland by McIntosh, Punch, Dorrer and Emond (2010), there are not a lot of accounts of surveillance that deal with care. McIntosh, Punch, Dorrer and Emond attribute the dearth of Surveillance Studies research devoted to care to the penchant for research focusing on the more ominous "big brother" and "panopticon" imagery associated with surveillance and control (2010: 290).…”
Section: Surveillance and Society 13(1) 52mentioning
confidence: 99%
“…Workers, according to McIntosh et al (2010), would prefer to emphasise their caring role. The softening of the edge of the message could thus perhaps be viewed as a symbolic representation of the ambivalence experienced by workers having to exercise control over young people.…”
Section: Figure 1: the Height Of Lazinessmentioning
confidence: 99%
“…The observational data showed that, apart from in Hillgrove, the young people did eat at the table with the workers. According to McIntosh et al (2010) and Punch et al (2009), young people can feel vulnerable at the table because they are monitored and assessed by not just the workers but also their fellow residents. The group dynamic in Hillgrove was described as unstable as it was a new resident group.…”
Section: Eating At the Tablementioning
confidence: 99%
See 2 more Smart Citations